CFD Analysis of Ilısu Dam Sluice Outlet - Aydin, M. Cihan; Ulu, Ali Emre; Karaduman, Çimen (Fırat University, 2018)
Ilisu Dam is one important energy projects in Turkey. After it is completed, it is expected that it will contribute to the country economy approximately $300 million annually. One of the most remarkable engineering designs of the dam is the conversion of diversion tunnels of 12 m in diameter and about 1 km in length into sluice outlet structure. In this study, the CFD simulation of Ilısu Dam sluice outlet were performed with 1/40 scale. The obtained CFD results were compared with physical model observations conducted by the State Water Works (SWW). A good agreement was achieved between both results, and some useful results of CFD were presented for design of the outlet.
Keywords: Engineering; Mühendislik